Scleral Lens Prescription and Management Practices: The SCOPE Study. (September 2018) - Harthan, Jennifer; Nau, Cherie B.; Barr, Joseph; Nau, Amy; Shorter, Ellen; Chimato, Nicolette T.; Hodge, David O.; Schornack, Muriel M.
Abstract : Objectives: To assess current scleral lens prescription and management practices by conducting an international online survey of eye care providers. Methods: The SCOPE (Scleral Lenses in Current Ophthalmic Practice: an Evaluation) study group designed and administered an online survey regarding current scleral lens prescription and management practices. The survey was open from January 15 to March 31, 2015, and generated 723 responses from individuals who had fit at least 5 patients with scleral lenses. Results: Respondents (n=663) prescribed scleral lenses that ranged from 15 to 17 mm in diameter (65%), smaller than 15 mm (18%), and larger than 18 mm (17%). More than 50 lens designs were identified. Average daily wearing time of 11.8 hr was consistent across 651 respondents, and 475/651 (73%) recommended midday removal on some, most, or all days. Most respondents recommended nonpreserved saline to fill the bowl of the lens before application (single-use vials, 392/653 [60%]; bottled products, 372/653 [57%]). A hydrogen peroxide-based disinfection system was the most commonly recommended care product (397/651 [61%]). Conclusions: A reasonable degree of consensus exists regarding some aspects of scleral lens prescription and management (average lens diameter, daily wearing time, and use of nonpreserved products for lens application). Further study is needed to develop evidence-based guidelines for scleral lens prescription and management. Abstract : Supplemental Digital Content is Available in the Text.